2010
DOI: 10.1093/europace/euq455
|View full text |Cite
|
Sign up to set email alerts
|

The role of pacemaker in hypersensitive carotid sinus syndrome

Abstract: Permanent pacemaker is an effective treatment for CSS. However, the recurrence of symptoms was two- to three-fold more frequent in patients with mixed CSS, probably due to the persistence of vasodepressor component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…282 Unlike AV block, the results of immunosuppression in patients with VA are controversial. Some studies have shown improvement with immunosuppression, 283 whereas others have shown no benefit and even harm due to worsening VA and aneurysm formation.…”
Section: 280-286mentioning
confidence: 99%
See 1 more Smart Citation
“…282 Unlike AV block, the results of immunosuppression in patients with VA are controversial. Some studies have shown improvement with immunosuppression, 283 whereas others have shown no benefit and even harm due to worsening VA and aneurysm formation.…”
Section: 280-286mentioning
confidence: 99%
“…417 Contraindications Syncope recurred in fewer patients treated with pacing than in untreated patients, with observation periods up to 5 years. 420,423 In 3 controlled, open-label trials, the relative risk reduction of syncope recurrence with pacemaker implantation was 76%. 409,[427][428][429] There are no large RCTs.…”
Section: Carotid Sinus Syndrome: Recommendationsmentioning
confidence: 99%
“…This quantification of the vasodepressor component is clinically relevant because it has been shown that pacemaker therapy is less effective when the vasodepressor effect is large, compared with that of predominant cardioinhibitory. 11,17,25,26 In an previous study, we found that syncope or presyncope recurred in 12% of patients affected by the dominant cardioinhibitory form and in 58% of those affected by the mixed form. 26 Lopes et al 17 showed that mixed CSS was the only independent predictor of symptom recurrence.…”
Section: Discussionmentioning
confidence: 90%
“…11,17,25,26 In an previous study, we found that syncope or presyncope recurred in 12% of patients affected by the dominant cardioinhibitory form and in 58% of those affected by the mixed form. 26 Lopes et al 17 showed that mixed CSS was the only independent predictor of symptom recurrence. Moreover, in the absence of a marked vasodepressor effect, most patients with prolonged asystole will benefit from simple, easy-to-implant, and less costly ventricular pacing.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation